Supplementation of fermented sorghum bread (kisra) with dehulled and defatted sesame flour - Mohammed, Sarah A.; Ali, Ali O.; Elkhalifa, Elamin A. (Gezira Journal of Agricultural Science, 2007)
In this study, dehulled sesame seeds obtained from Mamoun Elberier factory were defatted by solvent extraction to produce a dehulled and defatted sesame flour (DDSF). Proximate analyses were determined on both the dehulled sesame flour and dehulled and defatted sesame flour. The results indicated that there was an increase in the contents of protein, moisture, fiber and carbohydrates due to the defatting process. Flour obtained from the dehulled and defatted sesame seed was used to supplement staple Sudanese baked product sorghum kisra , in the ratios of 10%, 20% and 30%. The various replacement ratios resulted in an increase in the protein content of the kisra from 12.25% in control kisra to about 15.75%, 19.49%, and 23.20%, respectively. The above replacement ratios also resulted in a concomitant increase in the in-vitro protein digestibility of kisra breads. The sensory analysis indicated that there were no significant difference between kisra bread made from the various blends of sorghum and DDSF. However, panelists gave higher scores to the 10% sesame/sorghum supplemented kisra than the kisra made from the other ratios. Nutritional value of kisra can be enhanced by the addition of DDSF at a level of up to 30%.